Community Emergency Management During the 2005 Ambae Eruption, Vanuatu, SW Pacific. - Cronin, Shane J.; Nemeth, Karoly; Procter, John N.; Charley, Douglas T.; Harrison, Morris J; Garaebiti, Esline; Scott, Brad J.; Sherburne, Steve; Bani, Philipson; Lardy, Michel (Massey University., 2007)
No abstract available
Keywords: Community; Disaster management; Volcanic hazard; Melanesia; Pacific; Tradition; Caldera